Teaching History and Teaching History Research in the Age of Information and Communication Technologies - Gudín de la Lama, Enrique (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2014)
History teaching and learning processes and History research methods are essentially the same as always; however, the arrival of new technologies has helped to widen and deepen both historical research and the development of certain aspects of the acquisition of History-related skills.